Antibacterial potential of biosynthesized zinc oxide nanoparticles against poultry-associated foodborne pathogens: an in vitro study - Mohd Yusof, Hidayat; Abdul Rahman, Nor’Aini; Mohamad, Rosfarizan; Zaidan, Uswatun Hasanah; Samsudin, Anjas Asmara @ Ab Hadi (Multidisciplinary Digital Publishing Institute, 2021)
Since the emergence of multidrug-resistant bacteria in the poultry industry is currently a serious threat, there is an urgent need to develop a more efficient and alternative antibacterial substance. Zinc oxide nanoparticles (ZnO NPs) have exhibited antibacterial efficacy against a wide range of microorganisms. Although the in vitro antibacterial activity of ZnO NPs has been studied, little is known about the antibacterial mechanisms of ZnO NPs against poultry-associated foodborne pathogens. In the present study, ZnO NPs were successfully synthesized using Lactobacillus plantarum TA4, characterized, and their antibacterial potential against common avian pathogens (Salmonella spp., Escherichia coli, and Staphylococcus aureus) was investigated. Confirmation of ZnO NPs by UV-Visual spectroscopy showed an absorption band center at 360 nm. Morphologically, the synthesized ZnO NPs were oval with an average particle size of 29.7 nm. Based on the dissolution study of Zn2+, ZnO NPs released more ions than their bulk counterparts. Results from the agar well diffusion assay indicated that ZnO NPs effectively inhibited the growth of the three poultry-associated foodborne pathogens. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were assessed using various concentrations of ZnO NPs, which resulted in excellent antibacterial activity as compared to their bulkier counterparts. S. aureus was more susceptible to ZnO NPs compared to the other tested bacteria. Furthermore, the ZnO NPs demonstrated substantial biofilm inhibition and eradication. The formation of reactive oxygen species (ROS) and cellular material leakage was quantified to determine the underlying antibacterial mechanisms, whereas a scanning electron microscope (SEM) was used to examine the morphological changes of tested bacteria treated with ZnO NPs. The findings suggested that ROS-induced oxidative stress caused membrane damage and bacterial cell death. Overall, the results demonstrated that ZnO NPs could be developed as an alternative antibiotic in poultry production and revealed new possibilities in combating pathogenic microorganisms.